Region-specific foot pain and plantar pressure in people with rheumatoid arthritis: A cross-sectional study. (June 2018) - Stewart, Sarah; Carroll, Matthew; Brenton-Rule, Angela; Keys, Monique; Bell, Libby; Dalbeth, Nicola; Rome, Keith
Abstract: Background: It is unclear whether region-specific foot pain may influence plantar pressure in people with established rheumatoid arthritis. The aim was to determine the association between region-specific foot pain and region-specific plantar pressure. Methods: Twenty-one people with rheumatoid arthritis and 19 age- and sex-matched controls participated in this study. Self-reported foot pain in the toes, forefoot, midfoot and rearfoot was assessed using foot diagrams. Peak pressure and pressure time integrals for the toes, forefoot, midfoot and rearfoot were calculated using a pressure mat system. Differences in foot pain and pressure between the groups were calculated using appropriate regression models. To determine associations between region-specific pain and pressure, linear regression models were used while adjusting for body mass and participant group. Findings. Participants with rheumatoid arthritis were primarily elderly female with long disease duration. Compared to controls, participants with rheumatoid arthritis had higher odds of foot pain at the toes (Odds Ratio ( OR ) = 10.4, P  = 0.001), forefoot ( OR  = 6.3, P  = 0.006) and rearfoot ( OR  = 10.1, P  = 0.011). Participants with RA had higher peak pressure at the rearfoot ( P  = 0.003) and higher pressure time integrals at the forefoot ( P  = 0.005), midfoot ( P  = 0.016) and rearfoot ( P  < 0.001). After adjusting for body mass and participant group, peak pressure was significantly higher at the toes in those with midfoot pain and rearfoot pain. Interpretation: People with rheumatoid arthritis experience region-wide foot pain and demonstrate differences in pressure distribution compared to people without rheumatoid arthritis. Foot pain at the midfoot and rearfoot is also associated with increases in plantar pressure at the toes. Highlights: Foot pain is common at the toes, forefoot and rearfoot in rheumatoid arthritis. People with rheumatoid arthritis demonstrate differences in plantar pressure. Foot pain at the midfoot and rearfoot is associated with increased toe pressure.